2009
DOI: 10.4049/jimmunol.0803245
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Is a Regulator of NY-ESO-1-Specific CD8+ T Cell Expansion in Melanoma Patients

Abstract: The programmed death 1 (PD-1) receptor is a negative regulator of activated T cells and is up-regulated on exhausted virus-specific CD8+ T cells in chronically infected mice and humans. Programmed death ligand 1 (PD-L1) is expressed by multiple tumors, and its interaction with PD-1 resulted in tumor escape in experimental models. To investigate the role of PD-1 in impairing spontaneous tumor Ag-specific CD8+ T cells in melanoma patients, we have examined the effect of PD-1 expression on ex vivo detectable CD8+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
91
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(100 citation statements)
references
References 39 publications
9
91
0
Order By: Relevance
“…More recently, Fourcade et al reported that PD-1 expression was up-regulated on NY-ESO-1-specific CD8 + T cells in PBLs of melanoma patients, and PD-L1 pathway blockade enhanced the number of antigen-specific cytokine-producing CD8 + T cells (17). Here we have focused on coinhibitory pathway blockade ex vivo under different stimulating conditions and differentiation states of CD8 + T cells and observed distinct outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Fourcade et al reported that PD-1 expression was up-regulated on NY-ESO-1-specific CD8 + T cells in PBLs of melanoma patients, and PD-L1 pathway blockade enhanced the number of antigen-specific cytokine-producing CD8 + T cells (17). Here we have focused on coinhibitory pathway blockade ex vivo under different stimulating conditions and differentiation states of CD8 + T cells and observed distinct outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, spontaneous NY-ESO-1-specific CD8 + T cell responses were detectable directly ex vivo in peripheral blood of melanoma patients who were seropositive for NY-ESO-1 (17). In a recent report by Milne et al on a single NY-ESO-1-seropositive EOC patient, corresponding ascites and solid tumor specimen were shown to be enriched (up to 6%) for NY-ESO-1-tetramer-reactive CD8 + T cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…This approach allows us to probe exactly how PD-1 expression contributes to T-cell dysfunction without any other complicating factors. Most studies examining T-cell populations isolated from the peripheral blood of patients show that exhausted T cells have approximately three-to 10-fold more PD-1 than effector T cells (19,44,48). However, PD-1 expression on exhausted T cells can be modulated further by the severity of the infection, the size of the tumor (38), and the location of the T cell within the body (12,39).…”
Section: Discussionmentioning
confidence: 99%
“…Studying the effects of PD-1 blockade in restoring function to tumor-specific T cells also has resulted in inconsistent and conflicting data. In one study, interfering with PD-1/PD-L1 interactions resulted in augmented numbers of NY-ESO-1-specific T cells isolated from melanoma patients after 6 d of in vitro stimulation, and these T cells had a greater potential to produce effector cytokines than those expanded with PD-1 blockade (44,45). However, in vitro stimulation was required to observe the beneficial effects of PD-1 blockade, because no differences were noted when studying recently isolated PD-1 high NY-ESO-1-specific T cells, suggesting that the majority of tumor-specific T cells are unresponsive to PD-1 blockade.…”
Section: Discussionmentioning
confidence: 99%
“…A strong correlation between PD-1 ligand expression on tumor cells and unfavorable prognosis has been demonstrated for various cancers (38)(39)(40)(41)(42)(43)(44). Importantly, high expression of PD-1 on TILs has been reported (21,23,45), and PD-1 blockade has been shown to enhance the frequency of cytokine-producing cells (45). Currently, two humanized monoclonal antibodies against PD-1, ONO-4538/MDX-1106 and CT011, are in clinical trials for treatment of cancer and HCV infection.…”
Section: Overexpression Of Inhibitory Receptors On Exhausted T Cellsmentioning
confidence: 97%